Multi-oil fat emulsion improves postoperative nutritional status and reduces complications in patients with hilar cholangiocarcinoma - Tong, Yang; Bai, Sijia; Bi, Ting; Jin, Luyuan; Tang, Yufu; Zhou, Yinghui; Feng, Xiaodong; Zhang, Wei (Frontiers in Nutrition, 2025)
IntroductionHilar cholangiocarcinoma (HCCA) is a common and complex biliary tract tumor often accompanied by malnutrition and a high risk of postoperative complications. Effective nutritional support is critical for improving prognosis. This study aimed to investigate the effects of multi-oil fat emulsion on postoperative nutritional status, liver function, inflammatory response, and complication rates in patients with HCCA.MethodsA total of 88 patients with HCCA who underwent radical resection at our hospital between January 2022 and February 2024 were enrolled and randomly divided into two groups. The control group received 20% medium/long-chain fat milk injection, while the observation group received multi-oil fat milk injection, both combined with amino acid glucose solution for five consecutive days. Nutritional indices [albumin (ALB), hemoglobin (Hb), total protein (TP)], liver function indices [alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TBIL)], inflammatory markers [C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6)], and postoperative complications were assessed.ResultsAfter intervention, both groups showed improved nutritional and liver function indices and reduced inflammatory markers compared with baseline (all P<0.01). The observation group demonstrated significantly higher ALB, Hb, and TP levels and lower ALT, AST, TBIL, CRP, TNF-α, and IL-6 levels than the control group (all p < 0.01). The incidence of complications was significantly lower in the observation group (4.54%) compared with the control group (20.46%) (p = 0.049).DiscussionMulti-oil fat emulsion provided superior benefits over conventional fat emulsion in enhancing postoperative nutritional status, improving liver function, and reducing systemic inflammation and complications in HCCA patients. These findings suggest that multi-oil fat emulsion may be a preferable option for postoperative parenteral nutrition in this population.